"Till the clouds roll by" - Whorf, Richard, 1906-1966; Kern, Jerome, 1885-1945; Connolly, Myles; Holloway, Jean.; Walker, Robert, 1918-1951; Allyson, June, 1917-2006; Garland, Judy.; Horne, Lena.; Shore, Dinah, 1917-1994; Sinatra, Frank, 1915-1998; Metro-Goldwyn-Mayer.; Loew's Incorporated; et al. ([Los Angeles, CA] : Loew's Incorporated, 1946)
A musical based on the life of American Broadway pioneer Jerome Kern, featuring renditions of the famous songs from his musical plays by contemporary stage artists, including a condensed production of his most famous show, Showboat.
Originally released as a motion picture in 1947.
"Based on the life and music of Jerome Kern."
June Allyson, Lucille Bremer, Judy Garland, Kathryn Grayson, Van Heflin, Lena Horne, Van Johnson, Tony Martin, Dinah Shore, Frank Sinatra, Robert Walker.
Cinematographers, Harry Stradling, George J. Folsey; editor, Albert Akst; music, Jerome Kern; musical numbers staged and directed by Robert Alton.
In English; with optional Spanish dubbed version (only the narrative part).
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 15, 2016).
Keywords: Kern, Jerome, -- 1885-1945 -- Drama; Composers -- United States -- Drama; Musical theater -- United States -- Drama; Musical films; Biographical films; Feature films; Internet videos; Streaming video